Analysis of the role of acetylation in Giardia lamblia and the giardicidal potential of garcinol - Rocío G. Patolsky; Jerónimo Laiolo; Jerónimo Laiolo; Luciano Díaz-Pérez; Gabriel Luna Pizarro; Gonzalo F. Mayol; María C. Touz; Constanza Feliziani; Andrea S. Rópolo (Frontiers in Microbiology)
IntroductionPost-translational modifications of proteins provide cellular physiology with a broad range of adaptability to the external environment flexibly and rapidly. In the case of the protozoan parasite Giardia lamblia, the study of these modifications has gained relevance in recent years, mainly focusing on methylation and deacetylation of proteins. This study investigates the significance of acetylation in this protozoan parasite.MethodsThis study explores the role of acetylation in G. lamblia through a combination of immunofluorescence assays, manipulation of acetyltransferase enzymes, and the use of garcinol, an acetylation inhibitor, during the growth phase.ResultsThe acetylation of histone marks H3K9 and H3K27 occurs during growth and is followed by deacetylation during encystation. Transfections modifying acetyltransferase activity induced a latent cellular state, underscoring the importance of protein acetylation for parasite survival. Garcinol treatment during growth caused significant morphological changes, including plasma membrane blebbing and apoptotic-like bodies. Immunofluorescence revealed these bodies contained α-tubulin/acetylated α-tubulin and reactive oxygen species. Flow cytometry and Annexin V staining indicated early apoptosis within 24 hours of treatment. Additionally, garcinol led to the deacetylation of H3K9 and H3K27, with redistribution of tubulin and acetylated tubulin from microtubules to the cytosol. Significantly, garcinol prevented parasite recrudescence after treatment withdrawal.DiscussionThese results demonstrate that acetylation is essential for trophozoite survival and highlight the natural histone acetyltransferase inhibitor garcinol as a potential candidate for drug development against giardiasis, considering its giardicidal activity.